Study on Damage Mechanism of Waterflooding Development in Weizhou 11-4N Low-Permeability Oilfield. (16th February 2023) - Zhang, Yi; Zhu, Pengyu; Wei, Feng; Xue, Guoqing; Tang, Mingguang; Zhang, Congdi; Wang, Rui
Abstract : Weizhou 11-4N oilfield is a medium-low-porosity and low-permeability reservoir. The oilfield was initially developed by edge and bottom water energy and then transferred to water injection development. Affected by poor physical properties and heterogeneity of the reservoir, the oilfield appeared in the process of water injection development. When the water injection pressure increases, the water injection volume continues to decrease, and it is difficult to meet the injection requirements. On the basis of the analysis of reservoir heterogeneity, void structure, and clay minerals of reservoir, the water injection compatibility experiment, damage evaluation experiment, and nuclear magnetic resonance-velocity sensitivity experiments were carried out to clarify the damage in the process of oilfield water flooding development. Experiments show that the main causes of damage in Weizhou 11-4N oilfield water flooding development process are water quality incompatibility and strong velocity-sensitive damage. The determination of water type shows that the injected water and formation water are MgCl2 water type and NaHCO3 water type, respectively, under the classification of Surin water type, resulting in the formation of scale with calcium carbonate as the main component in the reservoir. Incompatibility of water quality is an important cause of reservoir damage and scaling. In the reservoir-sensitive flow experiment, the experimental core showed strong velocity sensitivity, the average velocity sensitivity damage rate was 466.31%, and the average critical velocity was 2.98 m/d. Nuclear magnetic resonance experiments show that the core has a significant decrease in average pore size after water flooding. The main damage range is the tiny throat of 0-2 μ m. In this paper, the main damage interval of velocity-sensitive damage in the Weizhou 11-4N area and the change trend of void structure after velocity-sensitive experiment are clarified by nuclear magnetic resonance and velocity sensitivity experiments. The main cause of block reservoir damage provides the basis for the oilfield to take targeted measures and provides a guarantee for the efficient development of the subsequent oilfield.